Diabetes associated with immune checkpoint inhibition: presentation and management challenges. Issue 9 (7th August 2018) - Galligan, A.; Xu, W.; Fourlanos, S.; Nankervis, A.; Chiang, C.; Mant, A. M.; Parente, P.; Rischin, D.; Krishnamurthy, B.; Sandhu, S.; Colman, P. G.
Abstract: Background: In recent years, immune checkpoint blockade has become a standard therapy for a wide range of cancers. Adverse events, including endocrinopathies, result from the induction of autoimmunity. Case report: We report a case series of nine individuals who presented with immunotherapy‐induced Type 1 diabetes between 2015 and 2017. Onset of diabetes occurred within 12 weeks of commencing therapy. Anti‐glutamic acid decarboxylase antibodies were present in six people. Retrospective testing of islet antibodies in pre‐treatment samples was possible in two people and this revealed anti‐glutamic acid decarboxylase seroconversion in the first and high anti‐glutamic acid decarboxylase titres pre‐ and post‐treatment in the second person. Six people had high risk human leukocyte antigen haplotypes. Clinical and genetic factors are described and compared with previously published cases. Conclusion: This rare form of iatrogenic diabetes is a result of an accelerated, fulminant islet autoimmunity induced by immune checkpoint inhibitors. High risk human leukocyte antigen haplotypes have been found in the majority of cases. The role of pre‐existing islet autoantibodies as a biomarker is not yet known. What's new?: Immune checkpoint inhibitor‐related Type 1 diabetes is rare in clinical trials, but case reports published between 2015 and 2017 suggest that real‐world incidence may be higher than previously anticipated. We describe nine cases of this life‐threatening immune‐mediated Type 1 diabetes. To our knowledge this is the largest series reported in the literature to date. Patients presented with fulminant, symptomatic hyperglycaemia within weeks of commencing immune checkpoint inhibitors. The unprecedented survival benefit seen with immune checkpoint inhibitors across many cancers is anticipated to result in their widespread use as a single agent and in combination with other cancer therapies in the near future.